Exploring the Effects of Farmland Transfer on Farm Household Well-Being: Evidence from Ore–Agriculture Compound Areas in Northwest China - Xueping Li; Xingmin Shi; Yuhan Qin (Land)
Due to long-term interactions between intensive resource exploitation and rapid social development, there are multiple challenges to maintaining and improving the well-being of farm households in ore–agriculture compound areas in Northwest China. However, few studies have focused on the effects of farmland transfer on farm household comprehensive well-being. This study collected 485 valid questionnaires through a structured questionnaire technique and then compared the well-being level and its five components between farm households who participated and did not participate in farmland transfer based on an index system of well-being. Further, a propensity score matching (PSM) method was used to estimate the net effects of farmland transfer on farm household well-being and its heterogeneity. The results showed the following. (1) Overall, farm household well-being in ore–agriculture compound areas in Northwest China was at a moderate level (mean value was 0.433), but there were large differences among its five components. The orders of the five components of well-being in the three study sites were consistent, and the well-being index of farm households participating in farmland transfer was generally greater than that of those not participating in farmland transfer. (2) The results of the PSM revealed that farmland transfer only increased the levels of well-being, security, and freedom of choice and action by 4.9%, 8.8% and 6.1%, respectively. (3) The younger the household heads and the higher their education levels, the greater the effects of farmland transfer on farm household well-being. Local government sectors should continue to improve their farmland transfer system and strengthen institutional innovation. Meanwhile, venerable groups’ well-being should be paid more attention in the process of farmland transfer.